PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX MANAGEMENT DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI PADA EMITEN BURSA EFEK INDONESIA SEKTOR PERBANKAN PERIODE 2020-2023 - Wijatmoko, Agus; Sumarno M, Sumarno M; Rely , Gilbert (Yayasan Nuraini Ibrahim Mandiri, 2024)
The research aims to analyze the influence of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on tax management in issuers listed on the Indonesia Stock Exchange in the banking sector for the period 2020-2023, with firm size as a moderating variable. The study utilizes panel data from 47 banking issuers over four years, resulting in a total of 188 data points analyzed using SPSS version 26. The findings indicate that GCG and CSR do not significantly affect tax management. Additionally, the size of the issuer does not moderate the influence of GCG and CSR on tax management, indicating that although issuers implement GCG and CSR practices, they have not yet been able to improve the effectiveness of tax management. This finding provides important insights for stakeholders and regulators in understanding the complexities of the relationship between corporate governance aspects, social responsibility, and tax management strategies in banking sector issuers.